BANDITRY OR INTERPERSONAL ANTAGONISMS?: SOCIAL uSES OF LOCAL ADMINISTRATION OF CRIMINAL JUSTICE IN CHILE: THE CASE OF LINARES. 1804-1871. - Brangier Peñailillo, Víctor (Revista de Historia Social y de las Mentalidades, 2024)
The article looks at the margins of  maneuverability that deployed subjects in  a rural community, in Linares, throughout  nineteenth century, on the stage of criminal  justice. We attempted to assess the social  use of justice that set the members of the  community, from the manipulation of the  concept of banditry, judicially reformulating  their interpersonal antagonisms. However,  this experience would have been suffered  turning points as the local justices permeate  pressure to impose a judicial bureaucracy,  driven by the state throughout the century.  The gradual legal subordination of the  lay judicial stages, would resenting the  malleability with which the residents lawsuit  in criminal justice, for definitions of banditry  would be imposed according to criminal law  was promulgated.
Keywords: Social Use of Justice; Banditry; interpersonal antagonisms; judicial bureaucratization